1995
DOI: 10.1099/0022-1317-76-9-2161
|View full text |Cite
|
Sign up to set email alerts
|

Complete nucleotide sequence of the herpesvirus simiae glycoprotein G gene and its expression as an immunogenic fusion protein in bacteria

Abstract: The nucleotide sequence of a 2384 bp portion within the unique short (Us) region of the herpesvirus simiae (simian herpes B virus; SHBV) genome is presented. A partial and a complete open reading frame (ORF) were found within this nucleotide sequence. The partial ORF encodes the C terminus (147 amino acids) of a protein kinase which is highly conserved in the herpes simplex virus type 1 (HSV-1) and type 2 (HSV-2) and simian agent 8 (SA8) U s regions. The complete ORF is located 3' to the partial ORF within the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
20
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 32 publications
2
20
0
Order By: Relevance
“…Specifically, HSV-2, pseudorabies virus, herpesvirus simiae, BHV-1, BHV-5 and ILTV gG homologues have not been shown to be integral components of the viral envelope although gG-related species have been identified in infected radiolabelled cells (Balachandran & HuttFletcher, 1985 ;Bennett et al, 1986 ;Keil et al, 1996 ;Kongsuwan et al, 1993 ;Slomka et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, HSV-2, pseudorabies virus, herpesvirus simiae, BHV-1, BHV-5 and ILTV gG homologues have not been shown to be integral components of the viral envelope although gG-related species have been identified in infected radiolabelled cells (Balachandran & HuttFletcher, 1985 ;Bennett et al, 1986 ;Keil et al, 1996 ;Kongsuwan et al, 1993 ;Slomka et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Of these, only four, gB, gD and the gH\gL complex, are essential for replication in vitro in cell culture, although it is presumed that the remainder serve important roles in vivo in viral pathogenesis. Glycoprotein G (gG) homologues have been identified in most alphaherpesviruses that have been examined (Colle et al, 1992 ;Crabb et al, 1992 ;Eberle et al, 1993 ;Ficorilli et al, 1995 ;Fukushi et al, 1997 ;Keil et al, 1996 ;Kongsuwan et al, 1993 ;McGeoch et al, 1987 ;Rea et al, 1985 ;Slomka et al, Fax j613 9416 2616. e-mail heidid!ariel.its.unimelb.edu.au associated species, gGV L and gGV S , are present in the virion as 140 and 20 kDa proteins, respectively. As gGS and gGV L do not appear to associate stably with other viral proteins, it is most likely that each species exists as a disulphide-linked homodimer.…”
Section: Introductionmentioning
confidence: 99%
“…The US4 ORF encodes a glycoprotein designated gG (27), which varies considerably among these viruses. All of the simian virus gGs are more similar to the gG of HSV-2 than to that of HSV-1, having a hydrophobic Nterminal signal sequence, two distinct regions of the extracellular domain separated by a proteolytic cleavage site, a transmembrane domain, and a highly charged cytoplasmic tail (27,36,34). The more N-terminal of the extracellular domains is relatively conserved in sequence, with six Cys residues and one N-linked glycosylation site being positionally conserved.…”
mentioning
confidence: 91%
“…When transmitted to nonmacaque primates, BV produces severe infections which usually involve the central nervous system and are frequently fatal (31,37,38). The molecular basis for the extreme neuropathology of BV in nonmacaque species is an intriguing question that remains unanswered.While sequences for a number of genes of BV have been reported (3,9,23,34,35,37), genomic characterization of BV has largely been limited to restriction analysis and gene mapping by hybridization with HSV gene probes (10,16,17). Such studies have suggested that, for the most part, the BV genome is colinear with that of HSV.…”
mentioning
confidence: 99%
See 1 more Smart Citation